Effectiveness of an Interface for Strategic Reading on University Students: an Exploratory Study - Luis Zarzosa Escobedo; David Luna Pérez; Tania De Parrés Fong; Esperanza Guarneros Reyes (Universidad Autónoma de Baja California, 2007)
A computer interface for training university students in reading comprehension of expository-argumentative texts is presented. A text is divided into several sections, for each of which several questions are presented; the reader must select an answer from among various choices and then a feedback screen is presented according to the answer. Two experiments were carried out to test the program's effectiveness. The first one compared the performance of 50 students in two successive but equivalent lessons. In the second one, the performance of 18 students after four lessons was compared with that of 15 students after a single lesson. There were statistically significant differences in both experiments that support the training effectiveness, although with noticeable variability between participants. The scope and limitations of the program due to the number of lessons and the size of the population sample in the second experiment are discussed in relation to the outcomes.